2016
DOI: 10.1080/14397595.2016.1192761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment with iloprost with or without bosentan on nailfold videocapillaroscopic alterations in patients with systemic sclerosis

Abstract: Our study confirms the effectiveness of bosentan, in combination with iloprost, in SSc microangiopathy observed to NVC. Moreover, the observed findings further support the role of CSURI in the evaluation and monitoring of SSc microangiopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(50 reference statements)
0
12
0
3
Order By: Relevance
“…A possible hypothesis explaining this discrepancy is that bosentan is mostly used in combination with other vasoactive drugs and topical therapies in daily clinical practice, some of which are prohibited in the RAPIDS studies. Supporting this idea, prostanoids do not show any effect on nailfold capillary changes, but the combination therapy of bosentan with prostanoids promotes the formation of new vasculature to a greater extent than the monotherapy of bosentan (21,23,24), suggesting that bosentan may render SSc endothelial cells responsive to prostanoids. Importantly, a possible synergy of bosentan with prostanoids is also implied in SSc-associated PAH (25).…”
mentioning
confidence: 53%
“…A possible hypothesis explaining this discrepancy is that bosentan is mostly used in combination with other vasoactive drugs and topical therapies in daily clinical practice, some of which are prohibited in the RAPIDS studies. Supporting this idea, prostanoids do not show any effect on nailfold capillary changes, but the combination therapy of bosentan with prostanoids promotes the formation of new vasculature to a greater extent than the monotherapy of bosentan (21,23,24), suggesting that bosentan may render SSc endothelial cells responsive to prostanoids. Importantly, a possible synergy of bosentan with prostanoids is also implied in SSc-associated PAH (25).…”
mentioning
confidence: 53%
“…26 It has been demonstrated that the association of iloprost with bosentan determines a progressive and lasting increase in fingertip blood perfusion, as well as nail-fold capillary numbers. 57,58 A recent retrospective observational study on 34 SSc patients with at least one active DU refractory to iloprost evaluated the effect of additional bosentan therapy. After 6 months, no new DUs had been recorded, and of 58 DUs at baseline 58% had completely healed, whereas 25% were partially healed.…”
Section: Combination Therapymentioning
confidence: 99%
“…Илопрост выпускается в двух формах -внутривенной и ингаляционной. Внутривенный илопрост изучался у пациентов с СЗСТ без ЛАГ для лечения поражения периферических сосудов, эффект был значительный, кроме того улучшалась переносимость физических нагрузок и гемодинамика по сравнению с исходными значениями [12,32]. Исследования ингаляционной формы илопроста при различных формах ЛАГ, включая СЗСТ-ЛАГ, продемонстрировали значительное улучшение ФК, переносимости физических нагрузок и гемодинамики по сравнению с плацебо [17].…”
Section: противовоспалительные препаратыunclassified
“…Улучшения гемодинамики или положительных результатов в отношении исходов не было, оценка эффективности у пациентов в ССД-ЛАГ не проведена ни в одном РКИ. Наиболее распространенными нежелательными эпизодами являлись головная боль, покраснение, боль в челюстях и диарея [10,12,11].…”
Section: противовоспалительные препаратыunclassified